Definizione lessicografica e definizione scientifica: Il problema della selezione contestuale e circostanziale - Paolini, Michele (Verbum – Analecta Neolatina, 2015)
We want to highlight the importance of some general questions about the research on definition. Mechanisms of selection based on context and circumstance determine the activation of operations aimed at specific parts of the global semantic field to which the single definitions relate. The definitions indicate the properties considered essential for these portions of the semantic field. In this regard, we have tested the existence of different levels of semantic organization of definitions. In particular, one explicit and one implicit. Finally, we observed several problems regarding the demarcation between lexicographical definition and definition of technical and scientific terms.